Simulation and analysis of geometric errors in high-precision bevel gear rolling testers - SHI Jian; LI Jinfeng; XIAO Jianming; ZHANG Jingcai (Jixie chuandong)
ObjectiveIn fields such as aviation, requirements for the vibration performance and service life reliability of bevel gear transmissions are continuously increasing, driving the upgrading of bevel gear rolling testers towards higher detection accuracy and multi-functionality. Currently, the shaft angle positioning accuracy of the world’s most advanced rolling testers has reached within 10 arcseconds, the adjustment accuracy of mounting distance and offset distance has achieved the micron level, and they are integrated with fatigue life and vibration testing functions, thus significantly increasing the difficulty of development.MethodsAgainst the background of developing high-precision bevel gear rolling testers, to ensure the geometric motion accuracy of the tester, a kinematic model of the rolling tester was established using multi-body system kinematics theory. Through homogeneous coordinate transformation, the influence of various errors in the kinematic chain of the rolling tester on the pose of the bevel gear under test was simulated. By extracting the geometric error items that affected the bevel vertex positioning and shaft angle accuracy of the bevel gear, a certain value was set for a single error item, its influence result was calculated, and then the reasonable range of each error item was analyzed and determined.ResultsThis method provides data support for error allocation and manufacturing accuracy assurance in the design and manufacturing process of rolling testers.